The Impact of Health Care Cost Increases on Fraud and Economic Waste - Boyer, Martin; Léger, Pierre-Thomas (Assurances et gestion des risques / Insurance and Risk Management, 2005)
In a model of imperfect information with costly auditing, we examine the effect of increases in health-care costs and general inflation on the optimal health-insurance policy and on waste. We show that in such a setting, individuals will buy more than full insurance. Moreover, as the cost of medical care increases, consumers (i.e., patients) are less likely to file unjustified claims while insurance providers audit with a lower probability. As a result, waste associated with costly auditing is reduced. We also show that a general increase in the opportunity cost of illness (reflected through lost earnings due to illness) also decreases waste, but not as much as health-care cost increases.